Llewellyn’s Lea*-Ways - Julius Cohen (Washington University Law Quarterly, 1962)
In the Oxford Universal Dictionary 1118 (3d ed. 1955), the word “lea” is defined as “Land that has remained untilled for some time; arable land under grass; land ‘laid down’ for pasture, grass-land.” Deliciously tempting, but quickly withdrawn from application here, is an alternative definition: “A measure of yarn of varying quantity.”
Keywords: Karl Llewellyn